Excessive erythrocyte ppix influences the hematologic status and iron metabolism in patients with dominant erythropoietic protoporphyria - Delaby, C; Lyoumi, S; Ducamp, S; Martin-Schmitt, C; Gouya, L; Deybach, J C; Beaumont, C; Puy, H (Cellular and Molecular Biology, 2015)
Partial deficiency of the last enzyme of the heme biosynthetic pathway (namely ferrochelatase, FECH) in humans is responsible for erythropoietic protoporphyria (EPP). This disorder is characterised by painful photosensitivity, due to excessive production of protoporphyrin IX (PPIX) by erythrocytes. Controversial hypotheses have been proposed to explain the hematologic and iron status of EPP patients. In the present work, we explored these parameters in 55 patients with dominant EPP recruited at the French Center of Porphyrias (Colombes, France) and confirmed by molecular analysis. Our data show that erythrocyte accumulation of PPIX in EPP patients influences hematologic and iron status. Patients studied had a mild anemia and thrombocytopenia, as shown by the downward shift of hematologic parameters, which positively correlated with the amount of erythrocyte PPIX. Interestingly, erythropoiesis did not seem to be limited by iron supply in patients, since serum iron and soluble transferring (Tf) receptor (sTfR) were normal. However, iron and Tf saturation negatively correlated with erythrocyte PPIX. Moreover, and as previously described in a mouse model of EPP, we noted a positive correlation between erythrocyte PPIX and Tf levels. Altogether, these results suggest a positive effect of PPIX on the synthesis on Tf, which could facilitate the mobilization of tissue iron stores to meet erythropoiesis requirement. Based on these observations and previous results in EPP mouse model, we propose that the PPIX-liver transferrin pathway plays a role in the orchestration of iron distribution between peripheral iron stores, the spleen and the bone marrow.